Supply Chain and Logistics Management in the Automotive Industry - Nhung, Tienne (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This examine investigates supply chain and logistics control practices inside the automobile enterprise, specializing in elements influencing deliver chain performance and organization profitability. The studies technique consists of stratified random sampling, device development, validation, and statistical analyses such as paired-samples t-take a look at, regression, ANCOVA, and Pearson correlational analyses. Descriptive records reveal key performance metrics, even as regression analyses show high-quality relationships between supply chain performance variables (inventory turnover, order achievement percentage, provider first-rate) and corporation profitability, controlling for corporation length. ANCOVA outcomes highlight mixed influences of deliver chain performance and organizational elements on profitability, while correlational analyses suggest robust positive correlations between stock turnover, order achievement percent, dealer high-quality, and organization profitability.